Association of inflammation geriatric nutritional risk index with all-cause and CVD mortality in patients with osteoarthritis - Cao, Gaohua; Zou, Yunxuan; Tan, Lei; Zhou, Yuanyuan; Xie, Shaodong; Jie, Ke; Chen, He (Frontiers in Nutrition, 2025)
BackgroundOsteoarthritis (OA) is a prevalent chronic disease affecting the elderly, with significant implications for morbidity and mortality. The geriatric nutritional risk index (GNRI) score is a tool for assessing the nutritional status of elderly patients and has been linked to mortality outcomes in various chronic diseases. However, its relationship with mortality in OA patients remains underexplored.ObjectiveTo evaluate the association between GNRI levels and all-cause and cardiovascular mortality in patients with OA, using data from NHANES (1999–2018).MethodsThis cohort study included 3,023 OA patients. GNRI was calculated using serum albumin levels and body weight data. Mortality outcomes were tracked until December 31, 2019, linking NHANES data with the National Death Index. Statistical analyses included Cox proportional hazards models, Kaplan–Meier survival curves, and subgroup analyses.ResultsHigh GNRI was significantly associated with reduced all-cause and cardiovascular mortality, even after adjusting for potential confounders. The relationship between GNRI and all-cause mortality was nonlinear, with the most significant protective effect observed at GNRI values below 130.55. Subgroup analysis revealed that the effect of GNRI on mortality risk was more pronounced in individuals aged 65 or older and non-Hispanic White people.ConclusionGNRI is a valuable prognostic tool for predicting mortality risk in OA patients. This study highlights the importance of incorporating nutritional assessments into the management of OA, particularly for high-risk populations. Future research should explore the potential benefits of nutritional interventions based on GNRI levels in reducing mortality among OA patients.